Chryseobacterium Gleum Urinary Tract Infection - T.G, Ramya; Baby, Sabitha; Das, Pravin; R.K, Geetha (Genes Review, 2015)
Introduction: Chryseobacterium gleum is an uncommon pathogen in humans. It is a gram negative, nonfermenting bacterium distributed widely in soil and water. We present a case of urinary tract infection caused by Chryseobacterium gleum in a patient with right lower ureteric calculi. Case presentation: This case describes a 62- year-old male admitted for ureteric calculi to the Department of Urology in a tertiary care hospital in Kerala. A strain of Chryseobacterium gleum was isolated and confirmed by MALDI-TOF MS .The bacterium was sensitive to Piperacillin-Tazobactum (100/10µg ), Cefotaxime(30µg),Ceftazidime(30 µg ) and Ofloxacin(30 µg). It was resistant to Nitrofurantoin (300µg),Tobramycin(10µg),Gentamicin(30µg),Nalidixic acid(30µg) and Amikacin(30µg). Conclusion: Chryseobacterium gleum should be considered as a potential opportunistic and emerging pathogen. Resistance to a wide range of antibiotics such as aminoglycosides, penicillin, cephalosporins has been documented. In depth studies on Epidemiological, virulence and pathogenicity factors needs to be done for better diagnosis and management.